Stochastic Stability of the non linear epidemic model with temporary immunity - Laid, Chahrazed (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
In this paper, addresses a time-delayed epidemiologic model by experi- encing the disease; whenever the quarantine will return to the susceptible. First, the equilibrium and global stabilities of the endemic equilibrium. Second, Stochastic Stability. Finally, the equilibrium and stability of the epidemic model with age.